APPLICATION OF THE EDUTAINMENT METHOD TO IMPROVE STUDENT LEARNING OUTCOMES - Bali, Muhammad Mushfi El Iq; Hishnuddin, As’ad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research is motivated by the problem of learning inequality between conditions that should and do not match expectations, one of which is caused by the teacher's method of teaching, which still often uses the conventional method, namely the expository method. The expository method is a learning method that only prioritizes students' understanding verbally so that students become bored and less active in class, as well as has an impact on decreasing student learning outcomes. The purpose of this research is to improve student learning outcomes by using the edutainment method. The Edutainment method is a learning method which is a combination of the concept of play and student interactive media, thus creating an interactive and innovative closeness between the teacher and students when learning takes place. The research method uses descriptive qualitative methods, with the use of these methods through interviews. The theory is based on the edutainment method, which increases learning outcomes and makes it fun and comfortable in class. With this method, the teacher is expected to be able to create good interactions with his students so that they will feel valued and involved when learning takes place. The research data is solid writing aimed at improving students' learning outcomes in the first grade F at Madrasah Diniah Al-Insyiroh Karang Anyar Paiton Probolinggo. The research results from increased student learning outcomes in class Awaliah F Madrasah Diniah Al-Insyiroh Karang Anyar Paiton Probolinggo, which previously decreased using the edutainment method